Dental caries experience in preschool children of Bauru, SP, Brazil - Fábio Silva de Carvalho; Cristiane Alves Paz de Carvalho; Roosevelt da Silva Bastos; Angela Xavier; Sabrina Pulzatto Merlin; José Roberto de Magalhães Bastos (Universidade Estadual de Campinas, 2015)
Aim: The main purpose of this study was to evaluate dental caries experience and prevalence in three to six-yearold preschool children from three public kindergartens of the city of Bauru, SP, Brazil. Methods: The sample comprised 283 children (142 boys; 141 girls) aged 3 to 6 years old. For data analysis, the dmft (decayed, missing and filled teeth), Significant Caries Index (SiC Index), percentage of caries-free children, Gini Coefficient and Care Index were determined. Mann-Whitney and Kruskal-Wallis tests were used with 5% significance. Results: The mean (SD) dmft index was 1.40 (2.63). Among the examined children, 63.25% were caries-free. The decayed component comprised 77.28% of the dmft. The Care Index was 19.70%, indicating limited utilization of dental treatment by children. The SiC index was 4.11 and the Gini Coefficient was 0.78 in the survey. The results showed that there were no statistically significant differences in the prevalence of the disease between the ages and between males and females. Conclusions: Dental caries experience and prevalence in preschool children were considered low in this study and the occurrence of polarization of the disease was identified.